Marine n-3 polyunsaturated fatty acids: a potential role in the treatment of sarcopenia. (April 2013) - Gray, Stuart; Da Boit, Mariasole
Sarcopenia is the age-related loss of muscle mass that results in a reduction in skeletal muscle function, quality of life and an increased risk of falls. Older muscle has an 'anabolic resistance' to both nutrients and exercise, with the precise underlying mechanism still to be elucidated. The n-3 polyunsaturated fatty acids found in fish oil can be incorporated into the membranes of skeletal muscles, where they may have anti-inflammatory effects. This alteration in muscle membrane fatty acid composition may have anabolic effects in aging muscle and, thus, be useful in the treatment of sarcopenia.